A new supramolecular tecton: the crucial impact of the polycation charge and geometry of H-bonds on the structure and properties of halometallates in the solid state - Shestimerova, Tatiana A; Medved'ko, Aleksei V; Bykov, Mikhail A; Kalinin, Mikhail A; Metlin, Mikhail T; Taydakov, Ilya V; Gontcharenko, Victoria E; Wei, Zheng; Dikarev, Evgeny V; Vatsadze, Sergey Z; Shevelkov, Andrei V (Dalton transactions : an international journal of inorganic chemistry, 2025)
A new tricationic organic supramolecular tecton has been designed and synthesized. Contrary to known mono- and dicationic species, this new molecule, being a "three-way connector", allows assembling infinite supramolecular sheets and nets upon interaction with appropriate inorganic counterpart complex anions. In this work, triprotonated 6-amino-5,7-dimethyl-1,3-diazaadamantane, comprising two secondary and one primary nitrogen atoms, is used as a trication to form hybrid compounds with iodometallate anions by forming five hydrogen bonds at a time. It is shown that the bulky cation works simultaneously as a spacer and a connector, such that the positions of inorganic [MI 6 ] 3− anions (M = Sb or Bi) in the crystal structures are defined by five hydrogen bonds and are well-separated from each other. The latter is considered as a prerequisite for the hybrid compounds to exhibit optical properties originating from the undisturbed electronic structure of individual inorganic anions. A new supramolecular tecton is designed that has the unique potential of assembling well-ordered supramolecular complexes by forming five directional hydrogen bonds at a time. It ensures an ordered distribution of inorganic halometallate anions.